치과위생사의 직장 내 성희롱 인식과 경험의 실태조사 - 오한나; Han-na Oh; 원영순; Young-soon Won (Han'guk Ch'iwisaeng Hakhoe chi, 2017)
Objectives: The purpose of this study was to examine dental hygienists` recognition and experiences about sexual harassment in the workplace and to provide the basic data for their perception improvement, prevention and coping plan about sexual harassment. Methods: A self-reported questionnaire was completed by 307 dental hygienists who work at dental hospitals and clinics in Jeollabuk-do area, a questionnaire survey was conducted from December 1 to 31, 2016. Results: The 40.7% of study subjects had the experience of sexual harassment. They were identified to have the experiences of verbal sexual harassment (29.6%), physical sexual harassment (27.0%) and visual sexual harassment (22.5%) in order. The factors affecting the experiences of sexual harassment were experience of sexual-harassment education and concept of sexual harassment. Conclusions: A customized sexual prevention education program for dental hygienists will need to be produced, not the universalized sexual prevention education. In addition, it is considered to be necessary to prepare for a program available for being sympathized and understood by all members in the workplace.